2019
DOI: 10.1002/advs.201902089
|View full text |Cite
|
Sign up to set email alerts
|

Nonleaching Antibacterial Concept Demonstrated by In Situ Construction of 2D Nanoflakes on Magnesium

Abstract: In bone implants, antibacterial biomaterials with nonleaching surfaces are superior to ones based on abrupt release because systemic side effects arising from the latter can be avoided. In this work, a nonleaching antibacterial concept is demonstrated by fabricating 2D nanoflakes in situ on magnesium (Mg). Different from the conventional antibacterial mechanisms that depend on Mg2+ release and pH increase, the nanoflakes exert mechanical tension onto the bacteria membranes to destroy microorganisms on contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…[ 1b,10 ] Since the mechanism does not involve chemical reagents, the potential toxicity and replenishment of antibacterial agents can be obviated. [ 11 ] Furthermore, it is highly desirable to design an antibacterial platform (materials) that can also serve as a quantitative bacteria sensor without involving tedious integration, but this type of rare “sense‐and‐treat” systems are frequently poorly designed and can hardly deliver the proper performance.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[ 1b,10 ] Since the mechanism does not involve chemical reagents, the potential toxicity and replenishment of antibacterial agents can be obviated. [ 11 ] Furthermore, it is highly desirable to design an antibacterial platform (materials) that can also serve as a quantitative bacteria sensor without involving tedious integration, but this type of rare “sense‐and‐treat” systems are frequently poorly designed and can hardly deliver the proper performance.…”
Section: Figurementioning
confidence: 99%
“…Stresses in various forms including physical interaction, [ 27 ] mechanical force, [ 11 ] and biochemicals [ 28 ] are exerted onto bacteria via either direct reaction or indirect interference mediated by the medium. Primary lesions take place first and activate the subsequent pathways modifying the physiological state of the bacteria on the protein and gene level.…”
Section: Figurementioning
confidence: 99%
“…Thus, the antibacterial effect of Sr–Zn0@CaP group was not caused by the presence of Sr, suggesting that intrinsic property and morphology of CaP coating may contribute to the observed antimicrobial property. Many precious reports have confirmed that the unique topological morphology and corrugated surface structure could damage the microorganism through intrinsic bacteriostatic process [ 39 , [45] , [46] , [47] , [48] ]. In addition, increased surface roughness at the microscale significantly inhibit bacterial adhesion and biofilm formation on its surface [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…After incubating at 37 °C for 1,3,6,12 and 18 h respectively, the alloy plates were fixed by 2.5% glutaraldehyde at 4 °C overnight, dehydrated sequentially by gradient ethanol (40, 60, 80, 90, 95, 98, and 100% v/v) gradually, and dried with a critical point drier. Finally, the samples were coated by gold before SEM observation [ 39 ] .…”
Section: Methodsmentioning
confidence: 99%
“…Rapid corrosion in aqueous solutions always hampers the applications of magnesium alloys in the automotive, aerospace, electronics industry, and biomedical field [ 1 6 ]. Nowadays, the concept of lightweight construction and equipment has been proposed for overcoming the energy and resources shortage in the development of our society [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%